Organic waste system assessment: Kaduwela Municipal Council - Jayathilake, Nilanthi; Drechsel, Pay; Dominish, E.; Carrard, N. (University of Technology Sydney. Institute for Sustainable Futures, 2021)
Rapid urbanization in Sri Lanka’s Kaduwela municipality generates an estimated 200 tons of solid waste daily, with 54–68% of it being biodegradable. Yet only 71 tons are collected, of which just 10 tons are composted. The remaining is largely sent to private operators for landfilling, costing the council LKR 166,500 per day. Despite attempts to promote composting and biogas production, weak operational practices and space constraints limit effectiveness. Compost sales remain low, averaging just 8–20 tons per month, with minimal revenue generation. Meanwhile, onsite sanitation systems serve nearly the entire municipality, as there is no sewer network. Septage collection mostly handled by private operators averages 181 m³/day, but nearly all of it is disposed at an overloaded pumping station not designed for such volumes. Only 27% of operational costs are recovered through service fees. Scenarios explored in the assessment show that if the compost plant were upgraded to its 20-ton capacity and integrated with dried faecal sludge (DFS) from septage, up to 13 tons of co-compost could be produced daily. However, this requires infrastructure investment, better composting practices, and coordination across public and private actors. Optimizing collection, improving compost quality, and exploring co-composting and biogas applications can enhance sustainability and cost recovery, while reducing environmental burdens from unmanaged urban waste.